TINGKAT PENGETAHUAN DAN STATUS EKONOMI MEMPENGARUHI MINAT PRA LANSIA DALAM MENGGUNAKAN GIGI TIRUAN SEBAGIAN LEPASAN - Rere Restu Cahyani; Herastuti Sulistyani; Suharyono Suharyono (Poltekkes Kemenkes Jambi, 2022)
Background: Various oral dental problems increase with age, including tooth loss. However, it has not been matched with the use of denture treatment to replace missing teeth. This study aimed to determine the relationship between knowledge and economic status in influencing the interest of the elderly in using removable dentures. Method: The study was using an analytical survey with a cross sectional design. A total of 65 Pre-elderly sample were gathered from Cipuruan Village. Data were collected using a questionnaire on knowledge, economic status and interest in using dentures. Data analysis using SPSS with Kendall-Tau statistical test (b). Results: 43% of pre-elderly in Cipurun Village had high school education, while 46.15%, had good knowledge and 55.38% had a low economic status. 54% of the pra elderly had moderate interest in using dentures. The significance test of knowledge level (p=0.000) and economic status (p=0.000) were associated with interest in using removable partial dentures. Conclusion: There is a significant relationship between knowledge and economic status with pre-elderly interest in using dentures.